Effect of subcutaneous tocilizumab treatment on work/housework status in biologic-naïve rheumatoid arthritis patients using inverse probability of treatment weighting: FIRST ACT-SC study - Yoshiya Tanaka; Hideto Kameda; Kazuyoshi Saito; Yuko Kaneko; Eiichi Tanaka; Shinsuke Yasuda; Naoto Tamura; Keishi Fujio; Takao Fujii; Toshihisa Kojima; Tatsuhiko Anzai; Chikuma Hamada; et al. (Arthritis Research & Therapy, 2018)
Abstract Background Following the onset of rheumatoid arthritis (RA), patients experience a functional decline caused by various joint symptoms which affects their activities of daily living and can lead to reduced work productivity. We evaluated the effect of a 52-week treatment with tocilizumab by subcutaneous injection (TCZ-SC) among biologic-naive Japanese house workers (HWs) and paid workers (PWs) with RA in a real-world clinical practice. Methods This multicenter, observational, prospective study enrolled 377 and 347 RA patients into TCZ-SC and conventional synthetic disease-modifying antirheumatic drugs (csDMARDs)-alone groups, respectively. The primary endpoint was the change in percentage of overall work impairment (OWI) among PWs at week 52 assessed using the Work Productivity and Activity Impairment Questionnaire (WPAI). Inverse probability of treatment weighting analyses were used to compare treatments. The Work Functioning Impairment Scale, disease activity, quality of life (QOL) measures, and safety were also assessed. Results The weighted change in OWI from baseline for PWs was −18.9% (TCZ-SC group) and −19.0% (csDMARDs group) at week 52, without a significant between-group difference (adjusted treatment difference 0.1, 95% confidence interval (CI) −6.3 to 6.5; P = 0.978). Changes in WPAI activity impairment in the overall group (between-group difference −6.4, 95% CI −10.7 to −2.2; P = 0.003) and HWs (−9.5, 95% CI − 16.0 to −2.9; P = 0.005) were significantly better with TCZ-SC than with csDMARDs at week 52. TCZ-SC-treated HWs showed significant improvement in all QOL assessments (Frenchay Activities Index, EuroQol 5 Dimension (EQ-5D), Japanese Health Assessment Questionnaire Disability Index (HAQ-DI), and 6-item Kessler scale (K6)) at week 52; PWs did not show any between-group differences for these QOL measures. Disease activity (Disease Activity Score 28-erythrocyte sedimentation rate, Clinical Disease Activity Index, and Simplified Disease Activity Index) and QOL measures (EQ-5D, HAQ-DI, and K6) improved over time in the overall group. No new safety concerns were raised with TCZ-SC. Conclusions Despite the lack of differences in OWI between groups at week 52, the overall group (particularly HWs) receiving TCZ-SC in addition to csDMARDs showed significant improvements in activity impairment, disease activity, and QOL versus those receiving csDMARDs alone. This study may promote the evaluation of work productivity improvements in HWs and PWs by RA treatment.